2011
DOI: 10.1002/asi.21474
|View full text |Cite
|
Sign up to set email alerts
|

Learning outcomes of information literacy instruction at business schools

Abstract: This paper reports results from an exploratory study investigating the factors affecting student learning outcomes of information literacy instruction (ILI) given at business schools. Specifically, the potential influence of student demographics, learning environment factors, and information literacy program components on behavioral, psychological, and benefit outcomes were examined. In total, 79 interviews with library administrators, librarians, teaching faculty, and students were conducted at three business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 24 publications
0
48
0
3
Order By: Relevance
“…Previous studies have suggested that if a person is information competent in one context, they will develop information‐competent behavior in the other contexts in which they are involved (Detlor, Julien, Willson, Serenko, & Lavallee, ). Our research confirmed that this is true but only at a basic level of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that if a person is information competent in one context, they will develop information‐competent behavior in the other contexts in which they are involved (Detlor, Julien, Willson, Serenko, & Lavallee, ). Our research confirmed that this is true but only at a basic level of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…6 Detlor et al offer a comprehensive model of assessment based on interviews, including a standardized IL testing instrument involving all factors affecting IL instruction among librarians, library administrators, faculty members, and students at business schools. 7 One frequently employed tool for analysis is the self-assessment test, sometimes used as the main method, 8 or combined with other data of a more objective nature. 9 A large number of works throughout the field make use of self-assessment as a diagnostic method that provides information about students' perceptions and needs to improve the training provided both in libraries and through IL programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, CI courses for continued education may be another option. Remarkably, a number of business schools have introduced information literacy courses in their regular curricula (Detlor et al, 2011;Booker et al, 2012). There is no excuse for LIS schools to give up CI training opportunities.…”
Section: Implications Of the Studymentioning
confidence: 99%